(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
When it comes to preparing workers with the industry-specific skills needed to keep up with an economy that is always changing, India’s vocational education system is crucial. Nevertheless, instructors’ low abilities frequently impede the efficacy of these programs in vocational training centres. The training that is given does not always meet the needs of the market since many teachers do not have up-to-date knowledge in technology, effective teaching methods, and experience in the field. Tackling these difficulties calls for an all-encompassing strategy to improve teacher skills. This gap can be filled by initiatives like organised capacity-building programs, collaborations with businesses, and the adoption of contemporary pedagogical practices. Another way to keep teachers current with trends is to encourage them to participate in ongoing professional development and make use of digital resources. Improved vocational training and a more employable workforce that can fuel India’s long-term economic growth may both be achieved through a more robust instructional framework.